2006
DOI: 10.1038/labinvest.3700430
|View full text |Cite
|
Sign up to set email alerts
|

Nell-1 induces acrania-like cranioskeletal deformities during mouse embryonic development

Abstract: We previously reported NELL-1 as a novel molecule overexpressed during premature cranial suture closure in patients with craniosynostosis (CS). Nell-1 overexpression also results in premature suture closure/ craniosynostosis in newborn transgenic mice. On a cellular level, increased levels of Nell-1 induce osteoblast differentiation and apoptosis. In this report, mice over-expressing Nell-1 were examined during embryonic development as well as shortly after birth for further analysis of craniofacial defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
(86 reference statements)
1
23
0
Order By: Relevance
“…Overexpression of NELL1 increased osteoblast differentiation and reduced cell proliferation in transgenic mice, while downregulation of NELL1 using in vitro approaches demonstrated inhibited osteoblast differentiation and suggested that decreased levels of NELL1 protein lead to promoted cell proliferation at the suture line (Zhang et al, 2002). It has also been reported that overexpression of NELL1 promotes apoptosis in osteoblasts both in vitro and in vivo (Zhang et al, 2003), and that this apoptotic activity may be associated with the Fas signaling pathway (Zhang et al, 2006). In NELL1 6R mutant mice, loss of NELL1 expression was associated with reduced expression of genes encoding tumor necrosis factor receptor superfamily member 11b and extracellular matrix proteins (Desai et al, 2006), which have also been implicated in human carcinogenesis (Ingber, 2002;Rowinsky, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of NELL1 increased osteoblast differentiation and reduced cell proliferation in transgenic mice, while downregulation of NELL1 using in vitro approaches demonstrated inhibited osteoblast differentiation and suggested that decreased levels of NELL1 protein lead to promoted cell proliferation at the suture line (Zhang et al, 2002). It has also been reported that overexpression of NELL1 promotes apoptosis in osteoblasts both in vitro and in vivo (Zhang et al, 2003), and that this apoptotic activity may be associated with the Fas signaling pathway (Zhang et al, 2006). In NELL1 6R mutant mice, loss of NELL1 expression was associated with reduced expression of genes encoding tumor necrosis factor receptor superfamily member 11b and extracellular matrix proteins (Desai et al, 2006), which have also been implicated in human carcinogenesis (Ingber, 2002;Rowinsky, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, transgenic Nell1-overexpressing mice recapitulate craniosynostosis-like phenotypes [56]. Accordingly, several recent studies indicate that Nell1 exerts osteoinductive activity [55,57].…”
Section: Introductionmentioning
confidence: 99%
“…Nell1 is a large secretory glycoprotein, and was originally identified in craniosynostosis patients as being specifically upregulated within prematurely fusing sutures [53]. Nell1 deficiency severely disrupts bone growth, as mice with nonsense mutations in Nell1 die perinatally with major skeletal anomalies in the craniofacial complex, spine, and long bones [54,55]. Conversely, transgenic Nell1-overexpressing mice recapitulate craniosynostosis-like phenotypes [56].…”
Section: Introductionmentioning
confidence: 99%
“…(13) In addition, Nell-1 overexpression results in abnormal cartilage formation, (14) whereas loss of Nell-1 function results in reduced gene expression of extracellular matrix proteins critical for osteogenesis and chondrogenesis. (15) In this study we revealed roles for Nell-1 in the molecular regulation of chondrogenesis using ATDC5 cells, a murine embryonal carcinoma-derived chondroprogenitor cell line that undergoes a multistep chondrogenic differentiation process beginning with mesenchymal condensation and culminating in cartilage formation in vitro.…”
Section: Introductionmentioning
confidence: 99%